Women's Self-Concept after Becoming a Single Parent in Jambi City - Mawaddah, Nursalis; Wirman, Welly (Komunika, 2025)
This article discusses the self-concept of women after becoming single parents through four aspects of self-concept according to Berzonsky: physical, social, moral, and psychological. The phenomenon of divorce or the death of a husband often impacts the family's psychology, particularly the wife left behind. This study aims to analyze the self-concept of women after becoming single parents in the city of Jambi, using a qualitative method with a phenomenological approach and a snowball method for selecting informants. The informants are women who became single parents due to divorce or the death of their husbands. Data was collected through in-depth interviews, observations, and documentation, with triangulation techniques to ensure the validity of the data. The study results show that the self-concept of women after becoming single parents tends to be positive. The informants remain confident in their appearance, although they feel the need to maintain their behavior to avoid being misunderstood by others. Their relationship with their children tends to become closer, despite some initial adaptation problems. Spiritually, the informants feel the need to be closer to God and believe that they are strong and capable of supporting their children. Psychologically, most informants feel stressed and sad after separating from their husbands.